Effect of emoxipine on cytotoxicity of peripheral blood mononuclears under cultivation with cytarabine and cyclocytidine - Nizheharodava, Darya B.; Zafranskaya, Marina M.; Kvasyuk, Eugenii I.; Sysa, Aliaksei G. (Experimental Biology and Biotechnology, 2021)
Taking into account the special role of oxidative stress that increases during cancer chemotherapy, the effect of the antioxidant emoxipine on peripheral blood mononuclears was studied under conditions that simulate the cytotoxic effects of antimetabolites of a number of modified cytidine nucleosides in relation to the tumor cell line K562. Lymphoid cells were also a source for subsequent modelling of the immune response to the cancer. It was found that neither the modified nucleosides themselves nor their combination with emoxipine caused changes in IL-2-stimulated cytotoxicity of lymphoid cells in relation to K562 tumor cell line. A study of the expression of the CD107a marker showed a significant stimulating effect of 1 µmol/L of citarabine on the activation of subpopulations of T-lymphocytes (CD3+ ) and cytotoxic T-lymphocytes (CD3+ CD8+ ).